2006
DOI: 10.1109/tsp.2005.863012
|View full text |Cite
|
Sign up to set email alerts
|

A pseudorandom postfix OFDM modulator - semi-blind channel estimation and equalization

Abstract: Abstract-This paper details a new orthogonal-frequency-division-multiplexing (OFDM) modulator based on the use of a pseudorandom postfix (PRP)-OFDM and discusses low-complexity equalization and channel estimation/tracking architectures. The main property of this new modulation scheme is the ability to estimate and track the channel variations semi-blindly using order-one statistics of the received signal. Compared with known cyclic prefix OFDM (CP-OFDM) pilot-symbol-assisted modulation (PSAM) schemes, the pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 23 publications
0
44
0
2
Order By: Relevance
“…Although the mobile communication applications mentioned above are all based on cyclicprefix OFDM (CP-OFDM) modulation techniques, several encouraging contributions have investigated some alternatives, e.g., zero-padded OFDM (ZP-OFDM) (Muquest et al, 2002;Muquet et al, 2000) and pseudo-random-postfix OFDM (PRP-OFDM) (Muck et al, 2006;2003) to replace the TD redundancy with null samples or known/pre-determined sequences. It has been found that significant improvements over CP-OFDM can be realized with either ZP-OFDM or PRP-OFDM (Muquest et al, 2002;Muquet et al, 2000;Muck et al, 2006;2003).…”
Section: Td-redundancy-based Cementioning
confidence: 99%
See 4 more Smart Citations
“…Although the mobile communication applications mentioned above are all based on cyclicprefix OFDM (CP-OFDM) modulation techniques, several encouraging contributions have investigated some alternatives, e.g., zero-padded OFDM (ZP-OFDM) (Muquest et al, 2002;Muquet et al, 2000) and pseudo-random-postfix OFDM (PRP-OFDM) (Muck et al, 2006;2003) to replace the TD redundancy with null samples or known/pre-determined sequences. It has been found that significant improvements over CP-OFDM can be realized with either ZP-OFDM or PRP-OFDM (Muquest et al, 2002;Muquet et al, 2000;Muck et al, 2006;2003).…”
Section: Td-redundancy-based Cementioning
confidence: 99%
“…It has been found that significant improvements over CP-OFDM can be realized with either ZP-OFDM or PRP-OFDM (Muquest et al, 2002;Muquet et al, 2000;Muck et al, 2006;2003). In previous works, ZP-OFDM has been shown to maintain symbol recovery irrespective of null locations on a multipath channel (Muquest et al, 2002;Muquet et al, 2000).…”
Section: Td-redundancy-based Cementioning
confidence: 99%
See 3 more Smart Citations